147k views
3 votes
Solve −4(x + 10) − 6 = −3(x − 2).

A. −40
B. −46
C. −52
D. 52

User Jimkberry
by
7.5k points

2 Answers

3 votes

Answer:

x = -52

Explanation:

-4(x+10)-6=-3(x-2)

Distribute -4 on the left side and -3 on the right side

-4x-40-6=-3x+6

Combine Like terms

-4x-46=-3x+6

Add 46 both sides

-4x=-3x+52

Add 3x to both sides

-1x=52

Divide by -1

x=-52

Hope this helps!!!! :)

User Azriel
by
7.5k points
7 votes
−4(x + 10) − 6 = −3(x − 2)
-4x-46=-3x+6
-x=52
x=-52

Thus, C would be the answer.
User Balki
by
7.8k points